Changes in Dietary Behavior among Coronary and Hypertensive Patients: A Longitudinal Investigation Using the Health Action Process Approach. Issue 3 (28th July 2015) - Steca, Patrizia; Pancani, Luca; Greco, Andrea; D'Addario, Marco; Magrin, Maria Elena; Miglioretti, Massimo; Sarini, Marcello; Scrignaro, Marta; Vecchio, Luca; Cesana, Francesca; Giannattasio, Cristina; Fattirolli, Francesco; et al.
<x xml:space="preserve">Abstract</x> Background Cardiovascular diseases (CVDs) are a major cause of worldwide morbidity and mortality. Nutrition plays an important role in the primary, secondary, and tertiary prevention of CVDs. The present longitudinal study used the Health Action Process Approach (HAPA) to investigate changes in dietary behavior in coronary patients (CPs) affected by acute coronary syndrome and hypertensive patients (HPs) affected by essential arterial hypertension. Methods CPs (N = 250) and HPs (N = 246) completed a questionnaire during three measurement points (baseline, 6‐month follow‐up, and 12‐month follow‐up). Statistical analyses included a repeated measures ANOVA and a multi‐sample structural equation model. Results HPs showed no changes in dietary behavior, whereas CPs improved their nutrition at 6 months and then maintained the healthier diet. The multi‐sample analysis indicated equivalence of the HAPA model for both patient populations. Conclusions These findings provide further evidence for the generalisability of the HAPA model, shedding light on dietary behavior among CVD patients and particularly on hypertensive patients which has received little attention. Moreover, the equivalence of the model suggests that the process of change is almost identical for individuals who are at high risk for a coronary event (i.e. HPs) and individuals who have already had the event (i.e. CPs).